Anticipation of Battery Condition Using Internet of Things. Issue 1 (February 2021) - Subramaniya Siva, A.; Parthasarathy, P.; Gijipriya, K.; Vinothini, N.; Stonier, Albert Alexander
Abstract: Nowadays batteries are becoming so popular because of its feature of storing electric energy enables portability of electric energy even in places where electric transmission lines cannot be laid effortlessly. They are playing a significant role in reaching the objective of universal access to environment friendly, reliable & affordable electricity services. But they are unable to serve their capacity because of their lack of proper monitoring & maintenance. In order to make the battery smarter & safer a system of remote monitoring of battery for determining the battery condition by measuring various parametric quantities of battery & to publicize the condition of battery, thereby maintaining the battery to serve its full capacity as well as to prevent the system from unexpected shutdown.